COVID-19 infection rates and social disadvantage in Ireland: An area-level analysis - Anne Devlin; Adele Whelan; Seamus McGuinness (The Economic and Social Research Institute (ESRI), 2024)
Existing research has shown that deprived areas were impacted to a greater extent by the COVID-19 pandemic in a multitude of ways but particularly in terms of the health impact. This research examines the health impact of the pandemic on people living in disadvantaged areas in Ireland. Health impacts are measured in terms of COVID-19 infection rates and ICU admission rates. The analysis is conducted by using area-level COVID-19 infection rate data at the Electoral Division (ED) level for Ireland and ED-level measures of deprivation based on the Pobal Haase Pratschke Relative Deprivation Index (Pobal HP Deprivation Index). Additional area-level information from the Census is also utilised. This work builds on previous work that examined the economic impact of COVID-19 on disadvantaged areas in Ireland in terms of pandemic-related unemployment.
Keywords: 330; Coronavirus; impact analysis; social situation; estimate; Ireland; Coronavirus; Wirkungsanalyse; Soziale Lage; Schätzung; Irland